Programa de enriquecimiento de ASAC (Asociación de Altas Capacidades) - Díaz Fernández, Olga; Bravo Pombo, Antón (FAISCA: Journal of High Abilities, 2002)
This article describes the Enrichment Program that the “Asociación de Altas Capacidades”( ASAC-High Capacities Association)has been carrying out in Santiago for almost a decade. Its origin and evolution untill present time are analised, paying special attention to every moment in the process concerning its evaluation.